Constructing issues in the media through metaphoric frame networks. (December 2018) - Dekavalla, Marina; Montagut, Marta
Highlights: Mixed metaphors in media discourse may not constitute different frames but combine in metaphoric frame networks. In these networks, different metaphors are connected hierarchically through relationships of elaboration and complementation. Metaphor is more than just a 'framing device' and delivers a more complex narrative about issues than traditional framing theory acknowledges. Abstract: This article draws on metaphor and framing theory to build on our understanding of how metaphor works to frame issues. It suggests that metaphors not only may operate as frames in themselves, but they can also combine in hierarchies of metaphoric frames which together co-construct superordinate metaphoric or non-metaphoric frames. Using insights from theory on mixed metaphor, metaphor hierarchies and scenarios, the article introduces the new concept "metaphoric frame networks" to explain interconnections and relationships between frames and metaphors within the same texts, which could at first appear to be unrelated. The article proposes a set of criteria by which a metaphoric frame network can be defined and distinguished from simpler frames. The argument of the article is then illustrated through an empirical analysis of the process frame in television coverage of the 2015 Catalan regional election.